Simulating groundstate and dynamical quantum phase transitions on a superconducting quantum computer - James Dborin; Vinul Wimalaweera; F. Barratt; Eric Ostby; Thomas E. O’Brien; A. G. Green (Nature Communications, 2022)
Strongly correlated condensed matter systems are among those for which quantum simulation should be able to give an advantage. Here, the authors use a translationally invariant tensor network technique to simulate a quantum critical system on a superconducting quantum processor.